Resveratrol inhibits inflammation after spinal cord injury via SIRT-1/NF-κB signaling pathway. (25th September 2021) - Zhao, Haosen; Mei, Xifan; Yang, Dongfang; Tu, Guanjun
Highlights: Resveratrol therapy improved the motor function of post-SCI rats. Resveratrol therapy improved the the survival of motor neurons and reduced lesion sizein the rats after SCI. SIRT-1/NF-κB signaling pathway was activated by resveratrol in the rats after SCI. Resveratrol treatment reduced inflammatory response and increased the expression of BDNF after SCI. Resveratrol upregulates SIRT-1 and inhibits inflammation after SCI in rats. Abstract: Spinal cord injury (SCI) can cause severe trauma to the central nervous system. Resveratrol has been widely studied for several of its medicinal properties, including anti-inflammatory, anti-aging and anti-oxidative effects. The regulation of SIRT-1 is thought to be related to the effects of resveratrol. As a downstream component of SIRT-1, NF-κB is one of the important signaling pathways that regulate the inflammatory response. Herein, we explored how treatment with resveratrol promoted recovery of motor function after SCI by activating the SIRT-1/NF-κB signaling pathway and inhibiting inflammation in rat models. Recovery of hind limb function was observed using the Basso, Beattie, and Bresnahan locomotor rating scale at different time points after SCI. Western blot analysis, immunofluorescence, Nissl staining and HE staining were utilized to observe the morphological characteristics of spinal cord tissue, as well as the expression of SIRT-1, NF-κB, TNF-α, IL-1β, IL-6 and brain-derived neurotrophic factor. Resveratrol treatment promoted motor function recovery, increased the expression of brain-derived neurotrophic factor, and reduced loss of motor neurons and lesion size among rats after SCI. Meanwhile, inflammatory response was inhibited as the SIRT-1/NF-κB signaling pathway was modulated. These results suggest that resveratrol can help achieve neuroprotective effect by inhibiting inflammation, regulated by the SIRT-1/NF-κB signaling pathway.